Real-world dose escalation of biologics for moderate-to-severe psoriasis in the United States. (31st December 2023) - Wu, Jashin J.; Patel, Manish; Zeng, Feng; Huang, Ahong; Pan, Xing; Cao, Yiwen; Chen, Naijun; Photowala, Huzefa; Garg, Vishvas; Crowley, Jeff
Abstract: Aim: To compare real-world dose escalation of risankizumab with other US Food and Drug Administration (FDA)-approved biologic treatments for management of moderate-to-severe psoriasis (PsO) in the United States. Methods: The Merative® MarketScan® Research Database was used to identify adults with ≥2 medical claims for PsO, ≥3 claims of the index biologic medication in the maintenance period, and ≥6 months continuous enrollment pre-induction and ≥6 months after initiation of the maintenance period. Dose escalation was defined as ≥2 dosing intervals where the average daily dose was ≥30% higher than the expected daily dose (per FDA-approved dosing). Comparisons between risankizumab and other cohorts were made using chi-square tests and logistic regression models. Results: At the 30% threshold, the percentage of patients with dose escalation in the full maintenance period was significantly lower with risankizumab (2.0%) compared with other drug classes (tumor necrosis factor, interleukin (IL)-12/23, IL-17, or other IL-23 inhibitors: 17.6%, 10.0%, 18.3%, or 7.1%, respectively; p < 0.0001 for each) and individual biologics (adalimumab, ustekinumab, secukinumab, ixekizumab, and guselkumab; 17.9%, 10.0%, 15.7%, 18.0%, and 7.2%, respectively; p < 0.0001). Conclusion: A significantly lower proportion of risankizumab-treated patients with PsO had dose escalations compared with patients treated with other biologics.